Helium rich stars produce the UV upturn. Issue Volume 15:Issue S341(2019) (November 2019) - De Propris, R.; Ali, S.; Bremer, M. N.; Phillipps, S.
Abstract: We measure the evolution of the UV upturn color for galaxies on the red sequence in clusters at 0 < z < 0.7 and to luminosity levels L ∼ L *. We show that the UV upturn color does not change until at least z = 0.55 but becomes significantly redder at z = 0.7. This is the first detection of evolution in the UV upturn. Our observations are inconsistent with all models proposed for its origin except the presence of a population of helium enriched stars, with helium abundances above 42 % and formed at z > 4.